Production and supply of high‐quality food protein for human consumption: sustainability, challenges, and innovations. (August 2014) - Wu, Guoyao; Fanzo, Jessica; Miller, Dennis D.; Pingali, Prabhu; Post, Mark; Steiner, Jean L.; Thalacker‐Mercer, Anna E.
Abstract : The Food and Agriculture Organization of the United Nations estimates that 843 million people worldwide are hungry and a greater number suffer from nutrient deficiencies. Approximately one billion people have inadequate protein intake. The challenge of preventing hunger and malnutrition will become even greater as the global population grows from the current 7.2 billion people to 9.6 billion by 2050. With increases in income, population, and demand for more nutrient‐dense foods, global meat production is projected to increase by 206 million tons per year during the next 35 years. These changes in population and dietary practices have led to a tremendous rise in the demand for food protein, especially animal‐source protein. Consuming the required amounts of protein is fundamental to human growth and health. Protein needs can be met through intakes of animal and plant‐source foods. Increased consumption of food proteins is associated with increased greenhouse gas emissions and overutilization of water. Consequently, concerns exist regarding impacts of agricultural production, processing and distribution of food protein on the environment, ecosystem, and sustainability. To address these challenging issues, the New York Academy of Sciences organized the conference "Frontiers in Agricultural Sustainability: Studying the Protein Supply Chain to Improve Dietary Quality" to explore sustainable innovations in food science and programming aimed at producing the required quality and quantity of protein through improved supply chains worldwide. This report provides an extensive discussion of these issues and summaries of the presentations from the conference.